The scruffy scoundrels : a new English translation of Gli Straccioni in a dual-language edition - Caro, Annibal, 1507-1566 (Italica Press Renaissance and modern plays series., 2016)
"Annibal Caro's 'Scruffy Scoundrels' presents a new English translation of 'Gli straccioni' in a dual-language edition with a new introduction and notes. This play provides a comic look at the chaos and corruption of Rome in the 16th century as powerful families attempted to effect reform"--